Conjuntos infinitos e funções bijetivas: uma abordagem na educação básica - Espírito Santo, Andressa do (2019)
This work proposes a classroom activity which is useful to help basic education students understand the formalization of infinite sets, through the concept of a bijective functions. Therefore, we begin the study presenting its theoretical basis through a detailed analysis on two fundamental concepts of mathematics and essential for definition of infinite sets: sets and functions. Following, we do a brief survey on the approach of these two concepts, as well as the existence or not of something related to infinite set in some national textbooks. We conclude the work with a proposal of a didactic sequence to be presented in high school with the objective of exploring the concept of bijection as the fundamental basis for the student to be able to differentiate an infinite set from a very large finite set.